2015
DOI: 10.4081/aiua.2015.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Comparing robotic, laparoscopic and open cystectomy: a systematic review and meta-analysis

Abstract: Objective: To conduct a systematic review and meta-analysis comparing outcomes between Open Radical Cystectomy (ORC), Laparoscopic Radical Cystectomy (LRC) and Robot-assisted Radical Cystectomy (RARC). RARC is to be compared to LRC and ORC and LRC compared to ORC. Material and methods: A systematic review of the literature was conducted, collating studies comparing RARC, LRC and ORC. Surgical and oncological outcome data were extracted and a meta-analysis was performed. Results: Twenty-four studies were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 35 publications
0
36
2
3
Order By: Relevance
“…These meta-analyses have concluded that RARC is associated with lower perioperative complications, reduced LOS, higher lymph node yield, lower transfusion requirement and equivocal PSM. The current meta-analysis comprising of pooled data with 239 patients from four RCTs does not support the conclusions from non-RCT meta-analysis [7, 8, 10, 20]. The results of the current meta-analysis show that RARC is associated with lower EBL, lower wound complications rate and longer operating times.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…These meta-analyses have concluded that RARC is associated with lower perioperative complications, reduced LOS, higher lymph node yield, lower transfusion requirement and equivocal PSM. The current meta-analysis comprising of pooled data with 239 patients from four RCTs does not support the conclusions from non-RCT meta-analysis [7, 8, 10, 20]. The results of the current meta-analysis show that RARC is associated with lower EBL, lower wound complications rate and longer operating times.…”
Section: Discussioncontrasting
confidence: 68%
“…Previously, there have been four other systematic reviews on this topic, however these included both retrospective and prospective comparative studies which were at high risk of selection, reporting and publication bias [7, 8, 10, 20]. These meta-analyses have concluded that RARC is associated with lower perioperative complications, reduced LOS, higher lymph node yield, lower transfusion requirement and equivocal PSM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The laparoscopic group showed shorter hospitalization time; however, the latter data could be also influenced by the different behaviour among the study centers; there was no difference considering all the other endpoints. As already reported in other studies comparing laparoscopic and robotic surgery, the rate of estimated blood loss and days of hospitalization are variable and often depend on the experience of the surgeon in laparoscopic and robotic techniques [29,30]. Most of the stenosis in our cohort involved the distal ureter.…”
Section: Discussionmentioning
confidence: 71%
“…Both laparoscopic radical cystectomy (LRC) and robot-assisted radical cystectomy (RARC) have longer operating time (RARC more than LRC), but studies show both produce better surgical outcomes with reduced blood loss and shorter length of stay in the hospital [49]. Another important point to factor in is the challenging and long learning curve associated with both LRC and RARC.…”
Section: Radical Cystectomymentioning
confidence: 99%